The Hoard of Rodotopi in Ioannina (Epirus, NW Greece) and the Copper Single-Edged Shaft-Hole Axes of the Early Bronze Age in the Helladic Area - Kleitsas, Christos N. (Archäologischer Anzeiger, 2019)
The hoard of Rodotopi in Ioannina is a set of four copper single-edged shaft-hole axes of the Early Bronze Age. Together with eight isolated similar artefacts from Epirus, they are classified in the type with the conventional name Veselinovo (after Vulpe). Its distribution is mainly located in the regions of Epirus, western-central Macedonia and in the neighbouring areas of Bulgaria or Romania. These were tools and/or weapons with a symbolic character, which were withdrawn from circulation (recycling) to become utilitarian or votive deposits. Furthermore, issues of production, consumption or use, combined with archaeometric data (metallography and chemical analysis), are examined to give a more comprehensive interpretation. This gives us an insight into the networks of ideas, commodities and know-how existing at an early period, when copper working was still at an experimental stage, in general.